The Royal Navy and maritime power in the twentieth century - Speller, Ian, 1969- (Cass series--naval policy and history, 2005)
This book provides an authoritative yet accessible analysis of the utility of maritime power and the role of navies by examining a series of case studies concentrating on the experience of the Royal Navy in the Mediterranean and Persian Gulf during.